Tea tree - an essential oil grown in Australia, and Zambia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Peter Aagaard grows tea trees on his farm in Zambia. The trees produce an oil which are used to make body care products, such as soaps and medicinal rubs.